2013
DOI: 10.1112/plms/pdt038
|View full text |Cite
|
Sign up to set email alerts
|

The homotopy theory of coalgebras over a comonad

Abstract: Abstract. Let K be a comonad on a model category M. We provide conditions under which the associated category M K of K-coalgebras admits a model category structure such that the forgetful functor M K → M creates both cofibrations and weak equivalences.We provide concrete examples that satisfy our conditions and are relevant in descent theory and in the theory of Hopf-Galois extensions. These examples are specific instances of the following categories of comodules over a coring (coring). For any semihereditary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…First, we allow the generators to be a class of maps; observe that any model category is (trivially) cofibrantly generated by its cofibrations and acyclic cofibrations. The reason for this convention is that past work has shown that even trivial Postnikov presentations can have nontrivial applications; see [11,Theorem 6.2].…”
Section: Fibrant Generation and Postnikov Presentations Of Model Catementioning
confidence: 99%
See 3 more Smart Citations
“…First, we allow the generators to be a class of maps; observe that any model category is (trivially) cofibrantly generated by its cofibrations and acyclic cofibrations. The reason for this convention is that past work has shown that even trivial Postnikov presentations can have nontrivial applications; see [11,Theorem 6.2].…”
Section: Fibrant Generation and Postnikov Presentations Of Model Catementioning
confidence: 99%
“…In [11], the authors provide conditions under which the left-induced model structure exists for such an adjunction.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…[Tate, by the way, worked with a commutative noetherian local ring Remark. In fact under very general conditions ( [38], § 3.1, [39], § 6.12), the bar construction associates to a morphism ϕ : A → B of suitable monoid objects, a pullback functor …”
Section: For Our Purposes It Is the Quotientmentioning
confidence: 99%